Optical pressure-sensitive adhesive sheet
The optical adhesive sheet with a photopolymerized base polymer and reactive surfactant maintains high initial adhesive strength and low water peel strength, addressing surfactant non-uniformity issues for improved water reworkability.
Patent Information
- Application Number
- JP2023099945
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2025-01-07
AI Technical Summary
Existing optical adhesive sheets with surfactants exhibit non-uniform surfactant dispersion due to poor compatibility with acrylic-based polymers, leading to reduced water releasability and impaired water reworkability.
An optical adhesive sheet containing a photopolymerized base polymer derived from a monomer component with a reactive surfactant, ensuring initial adhesive strength of 1.4N/10mm or more and water peel strength of 1.2N/10mm or less, with optional inclusion of non-reactive surfactants and hydrophilic oligomers to maintain uniform surfactant distribution.
The adhesive sheet maintains consistent water reworkability by ensuring high initial adhesive strength and low water peel strength, preventing surfactant non-uniformity and enhancing stability over time.
Smart Images

Figure 2025000221000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical pressure-sensitive adhesive sheet. [Background technology]
[0002] A display panel has a laminated structure including elements such as a pixel panel, a polarizing film, and a cover film. In the manufacturing process of a display panel, for example, an optically transparent adhesive sheet (optical adhesive sheet) is used to bond the elements included in the laminated structure.
[0003] On the other hand, optical adhesive sheets (optical adhesive sheets) having water peelability are known. The optical adhesive sheet is an optical adhesive sheet that can reduce the adhesive strength by infiltrating droplets of an aqueous liquid (water droplets, etc.) into the interface between the adherend and the adhesive sheet after being attached to the adherend. After being attached to the adherend, such an optical adhesive sheet can be easily peeled off from the adherend using water as necessary. For example, in the manufacturing process of a display panel, if a defect (such as misalignment) occurs in the attachment of the optical adhesive sheet to the adherend, the adhesive sheet can be peeled off from the adherend using water, and a replacement optical adhesive sheet can be used for the attachment (water reworkability). Such water peelable optical adhesive sheets for display panel use are described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-23679 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 describes an optical adhesive sheet containing an acrylic-based polymer and a surfactant. The surfactant is dispersed in a free state in the adhesive sheet. In this adhesive sheet, the presence of the surfactant on the adhesive surface results in water releasability. However, the surfactant has low compatibility with the acrylic-based polymer. Therefore, on the adhesive surface, the surfactants gradually gather together, causing uneven dispersion of the surfactant (non-uniformity of the surfactant). Due to the non-uniformity of the surfactant, the water releasability of the optical adhesive sheet is reduced and the water reworkability is impaired. The present inventors obtained this finding regarding the adhesive sheet of Patent Document 1.
[0006] The present invention provides an optical pressure sensitive adhesive sheet that can sustainably ensure good water reworkability. [Means for solving the problem]
[0007] The present invention [1] includes an optical adhesive sheet containing a base polymer, wherein the base polymer is a photopolymer of a monomer component containing a reactive surfactant, and the optical adhesive sheet has an adhesive strength Fn1 of 1.4 N / 10 mm or more in the initial peel test described below, and an adhesive strength Fw1 of 1.2 N / 10 mm or less in the first water peel test described below.
[0008] Initial peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the optical adhesive sheet is attached to an alkali glass plate prepared by the float method to obtain a laminate (preparation step). Next, the laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes (heating and pressurizing step). Next, the laminate is left to stand at room temperature for 30 minutes (standing step). Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling one end of the adhesive sheet piece in the length direction under conditions of 25°C, relative humidity of 50%, peeling angle of 180°, and pulling speed of 300 mm / min, to measure the adhesive strength (measurement step).
[0009] First water peel test: The method is the same as the initial peel test, except that a water supply step is performed after the standing step and before the measurement step. In the water supply step, 20 μL of distilled water is supplied onto the alkali glass plate of the laminate so that the distilled water contacts one end of the adhesive sheet piece in the longitudinal direction at the interface between the alkali glass plate and the adhesive sheet piece.
[0010] The present invention [2] includes the optical adhesive sheet according to the above [1], wherein the optical adhesive sheet further contains a non-reactive surfactant.
[0011] The present invention [3] includes the optical adhesive sheet according to the above [1] or [2], wherein the optical adhesive sheet further contains a hydrophilic oligomer.
[0012] The present invention [4] includes an optical adhesive sheet described in any one of [1] to [3] above, which has an adhesive strength Fw2 in the second water peel test described below, and the variation rate of the adhesive strength Fw2 relative to the adhesive strength Fw1 is 200% or less.
[0013] Second water peel test: The test was the same as the first water peeling test, except that in the standing step, the laminate was stood at room temperature for 72 hours.
[0014] The present invention [5] includes the optical adhesive sheet described in the above [4], which has an adhesive strength Fn2 in the following room temperature peel test, and the ratio of the adhesive strength Fw2 to the adhesive strength Fn2 is 0.4 or less.
[0015] Cold peel test: The test was the same as the initial peel test, except that in the standing step, the laminate was stood at room temperature for 72 hours. Effect of the Invention
[0016] As described above, the optical adhesive sheet of the present invention has a base polymer that is a photopolymerization product of a polymerizable component containing a reactive surfactant, and has an adhesive strength Fn1 of 1.4 N / 10 mm or more in an initial peel test and an adhesive strength Fw1 of 1.2 N / 10 mm or less in a first water peel test. That is, the optical adhesive sheet contains a base polymer having a portion derived from a reactive surfactant (surfactant-derived portion), and has an adhesive strength Fw1 (initial adhesive strength under water supply conditions) of 1.2 N / 10 mm or less with respect to an adhesive strength Fn1 of 1.4 N / 10 mm or more (initial adhesive strength under water non-supply conditions). After being bonded to an adherend, such an optical adhesive sheet can ensure sufficient water peelability and good water reworkability. In addition, since the surfactant is substantially fixed in the base polymer, the surfactant is prevented from becoming non-uniform on the adhesive surface of the optical adhesive sheet. This ensures the stability of water reworkability over time in the optical adhesive sheet. Therefore, the optical adhesive sheet of the present invention can continuously ensure good water reworkability. [Brief description of the drawings]
[0017] [Figure 1] 1 is a schematic cross-sectional view of an optical adhesive sheet according to one embodiment of the present invention. [Diagram 2] 1 is a schematic diagram of a water peeling test. [Diagram 3] This shows an example of a method of using the optical adhesive sheet shown in Fig. 1. Fig. 3A shows a step of attaching the optical adhesive sheet to a first adherend, Fig. 3B shows a step of joining the first adherend and the second adherend via the optical adhesive sheet, and Fig. 3C shows an aging step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] As shown in Fig. 1, an adhesive sheet 10 as one embodiment of the optical adhesive sheet of the present invention has a sheet shape of a predetermined thickness and extends in a direction (plane direction) perpendicular to the thickness direction H. The adhesive sheet 10 has an adhesive surface 11 and an adhesive surface 12 opposite to the adhesive surface 11. Fig. 1 exemplarily shows a state in which release liners L1, L2 are bonded to the adhesive surfaces 11, 12 of the adhesive sheet 10. The release liner L1 is disposed on the adhesive surface 11. The release liner L2 is disposed on the adhesive surface 12.
[0019] The adhesive sheet 10 is an optically transparent adhesive sheet (optical adhesive sheet). The adhesive sheet 10 is an optical adhesive sheet having water peelability. That is, the adhesive sheet 10 is an optical adhesive sheet that can reduce the adhesive force by infiltrating droplets of an aqueous liquid (water droplets, etc.) into the interface between the adherend and the adhesive sheet 10 after being attached to the adherend. The adhesive sheet 10 is also an optical adhesive sheet that is disposed, for example, at a light passing portion in a display panel. Examples of the display panel include a liquid crystal panel and an organic EL panel. The display panel has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover film. The adhesive sheet 10 is used, for example, in the manufacturing process of the display panel, to bond elements included in the laminated structure to each other.
[0020] The adhesive sheet 10 is a sheet-like pressure-sensitive adhesive. The adhesive sheet 10 contains a photopolymer as a base polymer. Specifically, the base polymer is a polymer obtained by photopolymerization of a polymerizable component including a reactive surfactant. Photopolymerization is a polymerization method in which a polymerization reaction of a polymerizable component is advanced by irradiation with active energy rays such as ultraviolet light. The adhesive sheet 10 has an adhesive strength Fn1 of 1.4 N / 10 mm or more in the initial peel test described below, and an adhesive strength Fw1 of 1.2 N / 10 mm or less in the first water peel test described below.
[0021] Initial peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the adhesive sheet 10 is attached to an alkali glass plate prepared by the float method to obtain a laminate (preparation step). In this step, the adhesive sheet piece is attached to the tin surface of the alkali glass plate (the same applies to other peel tests described later). Next, the laminate is heated and pressurized under conditions of 50°C, 0.5 MPa, and 15 minutes (heating and pressurizing step). Next, the laminate is left to stand at room temperature for 30 minutes (standing step). Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling one end of the adhesive sheet piece in the length direction under conditions of 25°C, relative humidity 50%, peel angle 180°, and pulling speed 300 mm / min, to measure the adhesive strength (measurement step). The method of the initial peel test is more specifically as described below in the examples.
[0022] First water peel test: The method is the same as the initial peeling test, except that the water supplying step is performed after the standing step and before the measurement step. In the water supplying step, 20 μL of distilled water is supplied onto the alkali glass plate of the laminate so that the distilled water contacts one end of the adhesive sheet piece in the length direction at the interface between the alkali glass plate and the adhesive sheet piece. Specifically, as shown in FIG. 2, 20 μL of distilled water 22 is supplied onto the alkali glass plate 21 of the laminate W so that the distilled water 22 contacts one end 10a in the length direction D of the adhesive sheet piece 10A at the interface B between the alkali glass plate 21 and the adhesive sheet piece 10A. More specifically, the method of the first water peeling test is as described later in the examples.
[0023] As described above, the adhesive sheet 10 has a base polymer that is a photopolymer of a polymerizable component containing a reactive surfactant, and has an adhesive strength Fn1 of 1.4 N / 10 mm or more in an initial peel test and an adhesive strength Fw1 of 1.2 N / 10 mm or less in a first water peel test. That is, the adhesive sheet 10 contains a base polymer having a portion derived from a reactive surfactant (surfactant-derived portion), and has an adhesive strength Fn1 (initial adhesive strength under water non-supply conditions) of 1.4 N / 10 mm or more and an adhesive strength Fw1 (initial adhesive strength under water supply conditions) of 1.2 N / 10 mm or less. In such an adhesive sheet 10, sufficient water peelability is exhibited after being attached to an adherend, and good water reworkability can be ensured. In addition, since the surfactant is substantially fixed in the base polymer, the surfactant is prevented from becoming non-uniform on the adhesive surface of the adhesive sheet 10. This ensures the stability of the water reworkability of the adhesive sheet 10 over time. Therefore, the adhesive sheet 10 can continuously ensure good water reworkability.
[0024] The adhesive strength Fn1 is preferably 1.6 N / 10 mm or more, more preferably 1.8 N / 10 mm or more, even more preferably 2.0 N / 10 mm or more, and also preferably 12.0 N / 10 mm or less, more preferably 10.0 N / 10 mm or less, and even more preferably 9.5 N / 10 mm or less. When the adhesive strength Fn1 is equal to or greater than the lower limit, the adhesive reliability of the adhesive sheet 10 to the adherend can be ensured. When the adhesive strength Fn1 is equal to or less than the upper limit, the low adhesive strength Fw1 can be ensured. Examples of methods for adjusting the adhesive strength Fn1 include selecting the type of base polymer in the adhesive sheet 10, adjusting the molecular weight, adjusting the degree of crosslinking, and adjusting the blending amount. Examples of these adjustment methods include selecting the type and adjusting the blending amount of the reactive surfactant, polyfunctional polymerizable compound (crosslinking agent), and polymerization initiator used when forming the base polymer. Examples of methods for adjusting the adhesive strength Fn1 include selecting the type of components other than the base polymer in the adhesive sheet 10, and adjusting the blending amount of the components. The components include oligomers (hydrophilic oligomers, hydrophobic oligomers), non-reactive surfactants, and silane coupling agents. The same adjustment methods are used for the adhesive strengths Fw1, Fn2, and Fw2 described below.
[0025] The adhesive strength Fw1 is preferably 1.0 N / 10 mm or less, more preferably 0.5 N / 10 mm or less, and even more preferably 0.25 N / 10 mm or less, from the viewpoint of improving the water peelability of the adhesive sheet 10 and realizing good water reworkability. The adhesive strength Fw1 is preferably 0.04 N / 10 mm or more, more preferably 0.06 N / 10 m or more, and even more preferably 0.1 N / 10 mm or more, from the viewpoint of suppressing lifting and peeling of the adhesive sheet 10 when unintended water adheres to the adhesive sheet 10 on the adherend.
[0026] The pressure-sensitive adhesive sheet 10 has a ratio (Fw1 / Fn1) of adhesive strength Fw1 to adhesive strength Fn1 of preferably 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and even more preferably 0.1 or less, and is preferably 0.004 or more, more preferably 0.01 or more. When the ratio (Fw1 / Fn1) is equal to or less than the upper limit, the water peelability of the pressure-sensitive adhesive sheet 10 can be improved to achieve good water reworkability. When the ratio (Fw1 / Fn1) is equal to or more than the lower limit, lifting and peeling of the pressure-sensitive adhesive sheet 10 when unintentional water adheres to the pressure-sensitive adhesive sheet 10 on the adherend can be suppressed.
[0027] The pressure-sensitive adhesive sheet 10 has an adhesive strength Fw2 in the second water peeling test described below, and the fluctuation rate of the adhesive strength Fw2 relative to the adhesive strength Fw1, expressed by the following formula, is preferably 200% or less, more preferably 120% or less, even more preferably 80% or less, and is also preferably -50% or more, more preferably 0% or more. When the fluctuation rate is equal to or less than the upper limit, the adhesive sheet 10 can ensure stability over time in water peelability and water reworkability. When the fluctuation rate is equal to or more than the lower limit, the adhesive sheet 10 can ensure stability over time in water peelability and water reworkability, while suppressing lifting and peeling of the adhesive sheet 10 when unintended water adheres to the adhesive sheet 10 on the adherend after a certain period of time.
[0028] Fluctuation rate (%) = [(Fw2-Fw1) / Fw1] x 100
[0029] Second water peel test: The test was the same as the first water peel test, except that in the resting step, the laminate was allowed to stand at room temperature for 72 hours.
[0030] The adhesive strength Fw2 is preferably 1.5 N / 10 mm or less, more preferably 1.2 N / 10 mm or less, even more preferably 0.9 N / 10 mm or less, even more preferably 0.6 N / 10 mm or less, and also preferably 0.04 N / 10 mm or more, more preferably 0.06 N / 10 mm or more, even more preferably 0.1 N / 10 mm or more. When the adhesive strength Fw2 is the upper limit or less, the adhesive sheet 10 can ensure stability over time in water peelability and water reworkability. When the adhesive strength Fw2 is the lower limit or more, the adhesive sheet 10 can be prevented from lifting and peeling when unintended water adheres to the adhesive sheet 10 on the adherend after a certain period of time.
[0031] The adhesive sheet 10 has an adhesive strength Fn2 in the room temperature peel test described below, and the ratio (Fw2 / Fn2) of the adhesive strength Fw2 to the adhesive strength Fn2 is preferably 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, even more preferably 0.1 or less, and is preferably 0.004 or more, more preferably 0.01 or more. When the ratio (Fw2 / Fn2) is equal to or less than the upper limit, the water peelability of the adhesive sheet 10 can be improved to achieve good water reworkability. When the ratio (Fw2 / Fn2) is equal to or more than the lower limit, lifting and peeling of the adhesive sheet 10 when unintentional water adheres to the adhesive sheet 10 on the adherend can be suppressed.
[0032] Cold peel test: The test was the same as the initial peel test, except that the resting time in the resting step was changed from 30 minutes to 72 hours.
[0033] The adhesive strength Fn2 is preferably 2 N / 10 mm or more, more preferably 2.1 N / 10 mm or more, even more preferably 2.2 N / 10 mm or more, and is preferably 15 N / 10 mm or less, more preferably 13 N / 10 mm or less, even more preferably 12.5 N / 10 mm or less. When the adhesive strength Fn2 is equal to or greater than the lower limit, the adhesive reliability of the adhesive sheet 10 to the adherend can be ensured. When the adhesive strength Fn2 is equal to or less than the upper limit, the low adhesive strength Fw2 can be ensured.
[0034] The adhesive sheet 10 is a sheet-like pressure-sensitive adhesive formed from an adhesive composition. The adhesive sheet 10 (adhesive composition) contains at least the above-mentioned base polymer.
[0035] The base polymer is an adhesive component that imparts adhesiveness to the adhesive sheet 10. Examples of base polymers include acrylic polymers, silicone polymers, polyester polymers, polyurethane polymers, polyamide polymers, polyvinyl ether polymers, vinyl acetate / vinyl chloride copolymers, modified polyolefin polymers, epoxy polymers, fluoropolymers, and rubber polymers. From the viewpoint of ensuring good transparency and adhesiveness in the adhesive sheet 10, the base polymer is preferably an acrylic polymer. The acrylic polymer is a copolymer of polymerizable components containing 50% or more by mass of (meth)acrylic acid ester. "(Meth)acrylic" means acrylic and / or methacrylic.
[0036] In this embodiment, the acrylic polymer is a polymerized product obtained by photopolymerization of a polymerizable component including a monofunctional monomer, a polyfunctional polymerizable compound as a crosslinking agent, and a reactive surfactant. The acrylic polymer is, for example, a polymerized product obtained by photopolymerization of a partial polymerized product (a mixture of a polymerized product of a monofunctional monomer and an unreacted monofunctional monomer) of a monofunctional monomer, a polyfunctional polymerizable compound, and a reactive surfactant.
[0037] Such an acrylic polymer includes a photopolymerized polymer (first photopolymerized polymer) having a photocrosslinked structure. The photocrosslinked structure is a structure in which a linear structure of units derived from a monofunctional monomer is crosslinked by a unit derived from a crosslinking agent. The base polymer may include a photopolymerized polymer (second photopolymerized polymer) that does not have such a photocrosslinked structure. The second photopolymerized polymer is a polymer of a monofunctional monomer.
[0038] The monofunctional monomer preferably contains a monofunctional (meth)acrylic acid alkyl ester, and more preferably contains a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 20 carbon atoms. The (meth)acrylic acid alkyl ester may have a linear or branched alkyl group, or may have a cyclic alkyl group (alicyclic alkyl group).
[0039] Examples of linear or branched (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and isooctyl (meth)acrylate.
[0113] Examples of suitable acrylates include but are not limited to, but are not limited to, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, and nonadecyl (meth)acrylate.
[0040] Examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl ester, (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring, and (meth)acrylic acid alkyl ester having a tricyclic or higher aliphatic hydrocarbon ring. Examples of the (meth)acrylic acid cycloalkyl ester include (meth)acrylic acid cyclopentyl, (meth)acrylic acid cyclohexyl, (meth)acrylic acid cycloheptyl, and (meth)acrylic acid cyclooctyl. Examples of the (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring include (meth)acrylic acid isobornyl. Examples of (meth)acrylic acid alkyl esters having three or more aliphatic hydrocarbon rings include dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.
[0041] The monofunctional (meth)acrylic acid alkyl ester may be used alone or in combination of two or more kinds. The monofunctional (meth)acrylic acid alkyl ester is preferably an acrylic acid alkyl ester having an alkyl group having 3 to 12 carbon atoms, and more preferably at least one selected from the group consisting of n-butyl acrylate (BA) and n-octyl acrylate (NOAA).
[0042] The proportion of monofunctional (meth)acrylic acid alkyl ester in the polymerizable component is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and more preferably 85% by mass or more, from the viewpoint of appropriately exhibiting basic properties such as adhesiveness in the adhesive sheet 10. This proportion is, for example, 99% by mass or less.
[0043] The monofunctional monomer may include a copolymerizable monomer that can be copolymerized with the monofunctional (meth)acrylic acid alkyl ester. The copolymerizable monomer may include, for example, a polar group-containing monomer. The polar group-containing monomer may include, for example, a hydroxy group-containing monomer, a carboxy group-containing monomer, and a monomer having a nitrogen atom-containing ring. The polar group-containing monomer is useful for modifying the acrylic polymer, such as ensuring the cohesive force of the acrylic polymer.
[0044] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl group-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (2HEA) and 4-hydroxybutyl acrylate (4HBA).
[0045] The proportion of the hydroxy group-containing monomer in the polymerizable component is preferably 1 mass % or more, more preferably 5 mass % or more, and even more preferably 7 mass % or more, from the viewpoint of ensuring the cohesive strength of the pressure-sensitive adhesive sheet 10. From the viewpoint of adjusting the polarity of the acrylic polymer (related to the compatibility between the various additive components in the pressure-sensitive adhesive sheet 10 and the acrylic polymer), this proportion is preferably 30 mass % or less, more preferably 20 mass % or less, and even more preferably 15 mass % or less.
[0046] Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0047] From the viewpoint of avoiding the risk of corrosion of the adherend by acid, the proportion of the carboxyl group-containing monomer in the polymerizable component is preferably 3 mass % or less, more preferably 1 mass % or less, even more preferably 0.5 mass % or less, and even more preferably 0.1 mass % or less.
[0048] Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, and acryloylmorpholine. The monomer having a nitrogen atom-containing ring is preferably at least one selected from the group consisting of N-vinyl-2-pyrrolidone (NVP) and acryloylmorpholine (ACMO).
[0049] The proportion of the monomer having a nitrogen atom-containing ring in the polymerizable component is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, from the viewpoints of ensuring the cohesive strength of the pressure-sensitive adhesive sheet and the adhesive strength of the pressure-sensitive adhesive sheet to the adherend. The proportion is preferably 10% by mass or less, more preferably 5% by mass or less, from the viewpoints of adjusting the glass transition temperature of the acrylic polymer and adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet with the acrylic polymer).
[0050] Examples of the polyfunctional polymerizable compound include polyfunctional monomers containing two or more ethylenically unsaturated double bonds in one molecule. Examples of the polyfunctional monomer include polyfunctional (meth)acrylates. Examples of the polyfunctional (meth)acrylates include bifunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional or higher polyfunctional (meth)acrylates.
[0051] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerin di(meth)acrylate, neopentyl glycol di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, dicyclopentenyl diacrylate, di(meth)acryloyl isocyanurate, and ethoxylated bisphenol A diacrylate (BPAEODE).
[0052] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.
[0053] Examples of tetrafunctional or higher polyfunctional (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol pentaacrylate, and dipentaerythritol hexa(meth)acrylate.
[0054] The polyfunctional polymerizable compound may be used alone or in combination of two or more kinds. The polyfunctional polymerizable compound is preferably dipentaerythritol hexaacrylate (DPHA).
[0055] The ratio of the polyfunctional polymerizable compound in the polymerizable component is preferably 0.01% by mass or more, more preferably 0.04% by mass or more, even more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, even more preferably 0.8% by mass or more, and is preferably 2% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1.2% by mass or less. When the amount of the polyfunctional polymerizable compound is equal to or more than the lower limit, the cohesive force of the adhesive sheet 10 can be increased, and the adhesive reliability after being attached to the adherend can be increased. When the amount of the polyfunctional polymerizable compound is equal to or less than the upper limit, the wettability of the adhesive sheet 10 to the adherend can be ensured, and the initial adhesive strength of the adhesive sheet 10 to the adherend can be ensured.
[0056] Examples of the reactive surfactant include anionic reactive surfactants, cationic reactive surfactants, and nonionic reactive surfactants.
[0057] An anionic reactive surfactant is a surfactant having reactivity due to the introduction of a radically polymerizable functional group into an anionic non-reactive surfactant. Examples of the anionic non-reactive surfactant include higher fatty acid salts, alkylaryl sulfonates, alkyl sulfate salts, polyoxyethylene alkyl ether sulfate salts, and polyoxyethylene alkylaryl ether sulfate salts. Examples of the higher fatty acid salts include sodium oleate. Examples of the alkylaryl sulfonates include sodium dodecylbenzene sulfonate. Examples of the alkyl sulfate salts include sodium lauryl sulfate and ammonium lauryl sulfate. Examples of the polyoxyethylene alkyl ether sulfate salts include sodium polyoxyethylene lauryl ether sulfate. Examples of the polyoxyethylene alkyl aryl ether sulfate salts include sodium polyoxyethylene nonylphenyl ether sulfate. Examples of the radically polymerizable functional groups include alkenyl groups, acryloyl groups, methacryloyl groups, vinyl groups, vinyl ether groups, and allyl ether groups.
[0058] A cationic reactive surfactant is a surfactant having reactivity due to the introduction of a radically polymerizable functional group into a cationic non-reactive surfactant. Examples of cationic non-reactive surfactants include alkyl trimethyl ammonium salts, alkyl benzalkonium salts, alkyl dimethyl benzyl ammonium salts, and alkyl dimethyl ethyl ammonium ethyl sulfates.
[0059] A nonionic reactive surfactant is a surfactant in which a radically polymerizable functional group is introduced into a nonionic nonreactive surfactant to give it reactivity. Examples of nonionic nonreactive surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, sorbitan higher fatty acid esters, polyoxyethylene sorbitan higher fatty acid esters, polyoxyethylene higher fatty acid esters, and glycerin higher fatty acid esters. Examples of polyoxyethylene alkyl ethers include polyoxyethylene lauryl ether and polyoxyethylene stearyl ether. Examples of polyoxyethylene alkyl phenyl ethers include polyoxyethylene octyl phenyl ether and polyoxyethylene nonyl phenyl ether. Examples of sorbitan higher fatty acid esters include sorbitan monolaurate, sorbitan monostearate, and sorbitan trioleate. Examples of polyoxyethylene sorbitan higher fatty acid esters include polyoxyethylene sorbitan monolaurate. Examples of polyoxyethylene higher fatty acid esters include polyoxyethylene monolaurate and polyoxyethylene monostearate. Examples of glycerin higher fatty acid esters include oleic acid monoglyceride and stearic acid monoglyceride.
[0060] The reactive surfactant may be used alone or in combination of two or more kinds. The reactive surfactant is preferably an anionic reactive surfactant. As the reactive surfactant, an anionic reactive surfactant and another type of reactive surfactant may be used in combination.
[0061] Commercially available products may be used as the reactive surfactant. Commercially available products of anionic reactive surfactants include, for example, Aqualon KH-10, KH-20, HS-05 and HS-10 manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Adeka Reasoap SR-10N, SR-20N, SDX-222 and SDX-223 manufactured by ADEKA Corporation, and Acrit 8WX-046-NS manufactured by Taisei Fine Chemical Co., Ltd. Other commercially available products of reactive surfactants include, for example, Aminoion RE1000L, RE3000MA and RE3000TG manufactured by Nippon Nyukazai Co., Ltd., Latemul PD-104, PD-105, PD-420, PD-430 and PD-450 manufactured by Kao Corporation, and Antox MS-60 and MS-2N manufactured by Nippon Nyukazai Co., Ltd.
[0062] The proportion of the reactive surfactant in the polymerizable component is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, even more preferably 0.3% by mass or more, and is preferably 0.9% by mass or less, more preferably 0.8% by mass or less, even more preferably 0.7% by mass or less. When the proportion of the reactive surfactant is equal to or greater than the lower limit, the adhesive strengths Fw1 and Fw2 of the pressure-sensitive adhesive sheet 10 can be reduced to ensure water peelability. When the proportion of the reactive surfactant is equal to or greater than the lower limit, the adhesive strengths Fn1 and Fn2 of the pressure-sensitive adhesive sheet 10 can be prevented from being excessively low.
[0063] In this embodiment, the acrylic polymer is formed by photopolymerization of the polymerizable component. The polymerizable component (including a monofunctional monomer and a polyfunctional polymerizable compound for introducing a crosslinked structure) may be polymerized in one step or in multiple steps. In the multistep polymerization method, first, a prepolymer composition containing a partial polymer (a mixture of a polymer of a monofunctional monomer and an unreacted monofunctional monomer) is prepared by polymerizing a monofunctional monomer (preliminary polymerization). Next, a polyfunctional polymerizable compound as a crosslinking agent and a reactive surfactant are added to the prepolymer composition, and then a polymerization reaction is allowed to proceed in a reaction system containing the partial polymer, the polyfunctional polymerizable compound, and the reactive surfactant (main polymerization). In the photopolymerization, a photopolymerization initiator may be used.
[0064] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator.
[0065] Examples of the radical photopolymerization initiator include an acylphosphine oxide photopolymerization initiator, a benzoin ether photopolymerization initiator, an acetophenone photopolymerization initiator, an α-ketol photopolymerization initiator, an aromatic sulfonyl chloride photopolymerization initiator, a photoactive oxime photopolymerization initiator, a benzoin photopolymerization initiator, a benzyl photopolymerization initiator, a benzophenone photopolymerization initiator, a ketal photopolymerization initiator, and a thioxanthone photopolymerization initiator.
[0066] Examples of the acylphosphine oxide photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethan-1-one. Examples of acetophenone photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of α-ketol photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin photopolymerization initiators include benzoin. Examples of benzyl photopolymerization initiators include benzyl. Benzophenone photoinitiators include, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and polyvinylbenzophenone. Ketal photoinitiators include, for example, benzyl dimethyl ketal. Thioxanthone photoinitiators include, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.The photopolymerization initiator may be used alone or in combination of two or more kinds. The photopolymerization initiator is preferably at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-1,2-diphenylethan-1-one, and 1-hydroxycyclohexyl phenyl ketone.
[0067] The amount of the photopolymerization initiator is preferably 0.03 parts by mass or more, more preferably 0.06 parts by mass or more, even more preferably 0.08 parts by mass or more, and also preferably 0.3 parts by mass or less, more preferably 0.2 parts by mass or less, per 100 parts by mass of the polymerizable component. When the amount of the photopolymerization initiator is equal to or more than the lower limit, a crosslinked network with sufficient crosslinking density is formed in the acrylic polymer, and the adhesive strength of the adhesive sheet 10 can be ensured. When the amount of the photopolymerization initiator is equal to or more than the lower limit, cohesive failure of the adhesive surface of the adhesive sheet 10 can be suppressed when the adhesive sheet 10 is peeled off from the adherend. This is useful, for example, for ensuring water reworkability. When the amount of the photopolymerization initiator is equal to or less than the upper limit, multiple occurrence of polymerization initiation points during photopolymerization can be suppressed, and a long-distance and continuous crosslinked network can be formed in the acrylic polymer. This is useful, for example, for ensuring initial adhesive strength. When the acrylic polymer is photopolymerized by preliminary polymerization and main polymerization, a photopolymerization initiator may be added after the preliminary polymerization and during the main polymerization. In this case, the amount of the photopolymerization initiator in the preliminary polymerization is preferably 0.03 parts by mass or more, more preferably 0.06 parts by mass or more, even more preferably 0.08 parts by mass or more, and also preferably 0.3 parts by mass or less, more preferably 0.2 parts by mass or less, per 100 parts by mass of the monofunctional monomer. The amount of the photopolymerization initiator (additional photopolymerization initiator) added during the main polymerization is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and also preferably 0.1 parts by mass or less, more preferably 0.07 parts by mass or less, and even more preferably 0.05 parts by mass or less, per 100 parts by mass of the polymerizable component.
[0068] The weight average molecular weight of the base polymer is preferably 500,000 or more, more preferably 800,000 or more, even more preferably 1,000,000 or more, and even more preferably 1,500,000 or more, from the viewpoint of ensuring the cohesive force in the pressure-sensitive adhesive sheet 10. The weight average molecular weight of the base polymer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0069] The glass transition temperature Tg1 of the base polymer is preferably 0° C. or lower, more preferably −20° C. or lower, even more preferably −40° C. or lower, and even more preferably −45° C. or lower, from the viewpoint of ensuring sufficient softness in the pressure-sensitive adhesive sheet 10. The glass transition temperature Tg1 is, for example, −80° C. or higher.
[0070] The glass transition temperature of the base polymer may be determined by the following Fox formula (theoretical value). The Fox formula is a relational expression between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of a polymer, Wi represents the weight fraction of a monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of a homopolymer formed from the monomer i. The glass transition temperature of a homopolymer may be determined by a literature value. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999) and "New Polymer Library 7: Introduction to Synthetic Resins for Paints" (Kyozo Kitaoka, Polymer Publishing Association, 1995). On the other hand, the glass transition temperature of a homopolymer of a monomer may be determined by a method specifically described in JP-A-2007-51271.
[0071] Fox formula 1 / (273+Tg)=Σ[Wi / (273+Tgi)]
[0072] The pressure-sensitive adhesive sheet 10 may contain an oligomer. Examples of the oligomer include hydrophilic oligomers and hydrophobic oligomers. The hydrophilic oligomer refers to an oligomer as a polymer of a monomer component containing 3% by mass or more of a hydrophilic monomer. The hydrophobic oligomer refers to an oligomer as a polymer of a monomer component containing less than 3% by mass of a hydrophilic monomer. The weight-average molecular weight of the oligomer is, for example, 1000 or more and 30000 or less. The weight-average molecular weight of the oligomer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0073] When the base polymer is an acrylic polymer, the oligomer is preferably an acrylic oligomer. That is, the hydrophilic oligomer is preferably a hydrophilic acrylic oligomer. The hydrophobic oligomer is preferably a hydrophobic acrylic oligomer. The acrylic oligomer is an oligomer as a polymer of a monomer component containing 50% by mass or more of an alkyl (meth)acrylate ester.
[0074] The hydrophilic acrylic oligomer is preferably a polymer of monomer components including a (meth)acrylic acid alkyl ester (chain alkyl (meth)acrylate) having a chain alkyl group, a (meth)acrylic acid alkyl ester (alicyclic alkyl (meth)acrylate) having an alicyclic alkyl group, and a hydrophilic monomer. Specific examples of the (meth)acrylic acid alkyl ester include the (meth)acrylic acid alkyl esters described above as monomer components of the acrylic polymer. Examples of the hydrophilic monomer include hydroxyl group-containing monomers and carboxyl group-containing monomers. Specific examples of the hydroxyl group-containing monomers and carboxyl group-containing monomers include the hydroxyl group-containing monomers and carboxyl group-containing monomers described above as monomer components of the acrylic polymer.
[0075] As the chain alkyl (meth)acrylate, methyl methacrylate (MMA) is preferred because it has a high glass transition temperature and is relatively compatible with the base polymer. The alicyclic alkyl (meth)acrylate is preferably at least one selected from the group consisting of dicyclopentanyl acrylate (DCPA), dicyclopentanyl methacrylate (DCPMA), cyclohexyl acrylate (CHA), and cyclohexyl methacrylate (CHMA). The hydrophilic monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl methacrylate (HEMA), 2-hydroxypropyl methacrylate (HPMA), and 4-hydroxybutyl methacrylate (HBMA). That is, the acrylic oligomer is preferably a polymer of monomer components including at least one selected from the group consisting of DCPA, DCPMA, CHA, and CHMA, at least one selected from the group consisting of HEMA, HPMA, and HBMA, and MMA.
[0076] The proportion of alicyclic alkyl (meth)acrylate in the monomer component of the hydrophilic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. The proportion of alicyclic alkyl (meth)acrylate being equal to or greater than the above lower limit helps to ensure the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10. The proportion of alicyclic alkyl (meth)acrylate being equal to or less than the above upper limit helps to ensure the compatibility of the acrylic polymer and the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10. The proportion of chain alkyl (meth)acrylate in the monomer component of the hydrophilic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. The proportion of the chain alkyl (meth)acrylate being equal to or greater than the above lower limit helps to ensure the compatibility of the acrylic polymer and the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10. The proportion of the chain alkyl (meth)acrylate being equal to or less than the above upper limit helps to ensure the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10. The proportion of the hydrophilic monomer in the monomer component of the hydrophilic acrylic oligomer is preferably 6% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 12% by mass or less. When the proportion of the hydrophilic monomer is equal to or greater than the above lower limit, the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10 can be ensured. When the proportion of the hydrophilic monomer is equal to or less than the above upper limit, the compatibility of the acrylic polymer and the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10 can be ensured.
[0077] The hydrophilic acrylic oligomer is obtained by polymerizing the monomer components of the acrylic oligomer (the same applies to the hydrophobic acrylic oligomer described below). Examples of the polymerization method include solution polymerization, active energy ray polymerization (e.g., UV polymerization), bulk polymerization, and emulsion polymerization. In the polymerization of the acrylic oligomer, a polymerization initiator may be used, and a chain transfer agent may be used for the purpose of adjusting the molecular weight.
[0078] The content of the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, even more preferably 0.4 parts by mass or more, and is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the base polymer. When the content of the hydrophilic oligomer is equal to or more than the lower limit, the adhesive strength of the pressure-sensitive adhesive sheet 10 (particularly the adhesive strength under a high-temperature and high-humidity environment) can be increased. When the content of the hydrophilic oligomer is equal to or less than the upper limit, the transparency of the pressure-sensitive adhesive sheet 10 can be ensured. When the pressure-sensitive adhesive sheet 10 contains too much oligomer, the compatibility of the oligomer decreases, which tends to increase the haze and decrease the transparency.
[0079] The hydrophobic acrylic oligomer is preferably a polymer of monomer components including a chain alkyl (meth)acrylate and an alicyclic alkyl (meth)acrylate. As the chain alkyl (meth)acrylate, MMA is preferred because it has a high glass transition temperature and is relatively compatible with the base polymer. As the alicyclic alkyl (meth)acrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate are preferred. That is, the acrylic oligomer is preferably a polymer of monomer components including one or more selected from the group consisting of dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and MMA.
[0080] The proportion of alicyclic alkyl (meth)acrylate in the monomer component of the hydrophobic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 90% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less. The proportion of alicyclic alkyl (meth)acrylate being equal to or greater than the above lower limit helps to ensure the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10. The proportion of alicyclic alkyl (meth)acrylate being equal to or less than the above upper limit helps to ensure the compatibility of the acrylic polymer and the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10. The proportion of chain alkyl (meth)acrylate in the monomer component of the hydrophobic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 90% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less. Having the proportion of the chain alkyl (meth)acrylate equal to or greater than the above lower limit helps ensure compatibility between the acrylic polymer and the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10. Having the proportion of the chain alkyl (meth)acrylate equal to or less than the above upper limit helps ensure the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10.
[0081] The content of the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, even more preferably 0.4 parts by mass or more, and is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less, relative to 100 parts by mass of the base polymer. When the content of the hydrophobic oligomer is equal to or more than the lower limit, the adhesive strength of the pressure-sensitive adhesive sheet 10 can be increased. When the content of the hydrophobic oligomer is equal to or less than the upper limit, the transparency of the pressure-sensitive adhesive sheet 10 can be ensured.
[0082] The pressure-sensitive adhesive sheet 10 preferably contains a hydrophilic oligomer, and more preferably contains a hydrophilic oligomer and a hydrophobic oligomer. The total content of the hydrophilic oligomer and the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 0.2 parts by mass or more, more preferably 0.6 parts by mass or more, and even more preferably 0.8 parts by mass or more, and is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the base polymer. When the total content of the oligomers is equal to or more than the lower limit, the adhesive strength of the pressure-sensitive adhesive sheet 10 can be increased. When the total content of the oligomers is equal to or less than the upper limit, the transparency of the pressure-sensitive adhesive sheet 10 can be ensured.
[0083] The pressure-sensitive adhesive sheet 10 preferably contains a non-reactive surfactant. Examples of the non-reactive surfactant include the anionic non-reactive surfactant and the non-ionic non-reactive surfactant described above with respect to the reactive surfactant. Examples of commercially available anionic non-reactive surfactants include Hitenol LA-10, LA-12, and LA-16 manufactured by Daiichi Kogyo Seiyaku Co., Ltd. Examples of commercially available non-ionic non-reactive surfactants include Rheodol TW-L120, L106, and TW-P120 manufactured by Kao Corporation, S-970, S-1170, and S-1570 manufactured by Mitsubishi Chemical Foods Corporation, and NIKKOL TW-10, TW-20, and BWA-5 manufactured by Nikko Chemicals Co., Ltd.
[0084] The proportion of the non-reactive surfactant in the pressure-sensitive adhesive sheet 10 is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.07% by mass or more, and is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, even more preferably 0.2% by mass or less. When the proportion of the non-reactive surfactant is equal to or greater than the lower limit, the adhesive strengths Fw1 and Fw2 of the pressure-sensitive adhesive sheet 10 can be reduced to ensure water peelability. When the proportion of the reactive surfactant is equal to or greater than the lower limit, excessive reduction in the adhesive strengths Fw1 and Fw2 of the pressure-sensitive adhesive sheet 10 in a high-temperature, high-humidity environment can be suppressed.
[0085] The pressure-sensitive adhesive sheet 10 may contain other components, such as a silane coupling agent, an ultraviolet absorbing agent, an antioxidant, and an anti-rust agent.
[0086] Examples of the silane coupling agent include silane coupling agents containing an epoxy group. Examples of the silane coupling agent containing an epoxy group include 3-glycidoxydialkyldialkoxysilane and 3-glycidoxyalkyltrialkoxysilane. Examples of the 3-glycidoxydialkyldialkoxysilane include 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane. Examples of the 3-glycidoxyalkyltrialkoxysilane include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. As the silane coupling agent, preferably, 3-glycidoxyalkyltrialkoxysilane is used, and more preferably, 3-glycidoxypropyltrimethoxysilane is used. The silane coupling agent may be used alone or in combination of two or more kinds. The proportion of the silane coupling agent in the adhesive sheet 10 is preferably 3 mass % or less, more preferably 1 mass % or less, even more preferably 0.1 mass % or less, and particularly preferably 0.0 mass %, from the viewpoint of suppressing the adhesion strength of the adhesive sheet 10 to glass and exhibiting good water peelability.
[0087] From the viewpoint of ensuring sufficient adhesion to the adherend, the thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 μm or more, more preferably 20 μm or more. From the viewpoint of the ease of handling and cutting of the pressure-sensitive adhesive sheet 10, the thickness of the pressure-sensitive adhesive sheet 10 is preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, even more preferably 200 μm or less, and even more preferably 150 μm or less.
[0088] The total light transmittance of the pressure-sensitive adhesive sheet 10 is preferably 90% or more, more preferably 92% or more, and is, for example, 100% or less. When the total light transmittance of the pressure-sensitive adhesive sheet 10 is equal to or more than the above lower limit, the pressure-sensitive adhesive sheet 10 can ensure the transparency required for an optical pressure-sensitive adhesive sheet for use in a display panel. The total light transmittance of the pressure-sensitive adhesive sheet 10 is, for example, 100% or less. The total light transmittance can be measured in accordance with JIS K 7375 (2008).
[0089] The release liner L1 is, for example, a transparent resin film having flexibility. Examples of the material of the release liner L1 include polyester resin, polyolefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, cellulose resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). From the viewpoints of transparency and strength, the material of the release liner L1 is preferably a polyester resin, and more preferably PET. The surface of the release liner L1 on the side of the pressure-sensitive adhesive sheet 10 is preferably subjected to a release treatment with a release treatment agent. Examples of the release treatment include a silicone release treatment, a long-chain alkyl acrylate release treatment, and a fluorine release treatment.
[0090] The release liner L2 is a flexible, transparent resin film. Examples of materials for the release liner L2 include the materials mentioned above for the release liner L1. From the viewpoints of transparency and strength, the material for the release liner L2 is preferably a polyester resin, more preferably PET. The surface of the release liner L2 on the side of the PSA sheet 10 is preferably release-treated with a release treating agent. Examples of the release treatment include the release treatments mentioned above for the release liner L1.
[0091] The adhesive sheet 10 can be produced, for example, as follows.
[0092] First, the pressure-sensitive adhesive composition is prepared. Specifically, a mixture (liquid) containing the monofunctional monomer and the photopolymerization initiator is irradiated with ultraviolet light to photopolymerize a portion of the monofunctional monomer in the mixture to obtain a prepolymer composition. Examples of light sources for ultraviolet light irradiation include ultraviolet LED lights, high-pressure mercury lamps, black light lamps, and metal halide lamps. In addition, in the ultraviolet light irradiation, a wavelength cut filter for cutting a portion of the wavelength range of the light emitted from the light source may be used as necessary. In the ultraviolet light irradiation, the illuminance is, for example, 5 to 200 mW / cm. 2 m, and the cumulative irradiation dose is, for example, 100 to 5000 mJ / cm 2 It is preferable to continue the ultraviolet irradiation until the viscosity of the composition reaches about 15 to 25 Pa·s. This viscosity is a value measured by a B-type viscometer under the conditions of rotor No. 5, rotor rotation speed of 10 rpm, and temperature of 30°C. The prepolymer composition contains a photopolymerized product of a monofunctional monomer (the second photopolymerized polymer) and a monofunctional monomer (residual monomer) that has not undergone a polymerization reaction. In addition, the prepolymer composition does not contain a solvent. Next, a multifunctional polymerizable compound, a reactive surfactant, and other components as necessary are added to the prepolymer composition. Examples of the other components include an additional photopolymerization initiator, a reactive surfactant, a silane coupling agent, and an antioxidant. This results in a pressure-sensitive adhesive composition. The pressure-sensitive adhesive composition does not contain a solvent, and is therefore a solvent-free pressure-sensitive adhesive composition.
[0093] Next, a pressure-sensitive adhesive composition is applied onto the release liner L1 to form a coating film, and then a release liner L2 is laminated onto the coating film on the release liner L1. Examples of methods for applying the pressure-sensitive adhesive composition include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating.
[0094] Next, the coating film between the release liners L1 and L2 is irradiated with ultraviolet light to photocure it, forming a pressure-sensitive adhesive layer. The ultraviolet light irradiation causes a polymerization reaction in the coating film in a reaction system containing the above-mentioned residual monomer and a polyfunctional polymerizable compound, and a first photopolymerized polymer having a photocrosslinked structure is formed. Thereafter, the pressure-sensitive adhesive layer may be dried by heating. The drying temperature is, for example, 80°C to 150°C. The drying time is, for example, 30 seconds to 10 minutes. The drying process allows the unreacted monomer in the pressure-sensitive adhesive layer to be volatilized and removed.
[0095] In this manner, adhesive sheet 10 can be manufactured in which adhesive surfaces 11, 12 are covered and protected by release liners L1, L2. Release liners L1, L2 are peeled off from adhesive sheet 10 as necessary when adhesive sheet 10 is to be used.
[0096] 3A to 3C show an example of a method of using the adhesive sheet 10. FIG.
[0097] In this method, first, as shown in Fig. 3A, the adhesive sheet 10 is attached to one surface in the thickness direction H of a member 31 (first adherend) (attaching step). Examples of the member 31 include a pixel panel and a polarizing film in a display panel. Through this step, the adhesive sheet 10 for bonding to another member is provided on the member 31.
[0098] In this step, if a defect (such as misalignment) occurs in the bonding of the adhesive sheet 10 to the member 31, the adhesive sheet 10 can be appropriately peeled off from the member 31 using water. For example, by infiltrating water droplets into the interface between the member 31 and the adhesive sheet 10, the adhesive strength of the adhesive sheet 10 can be reduced, and then the adhesive sheet 10 can be easily peeled off from the member 31. After peeling, the bonding step to the member 31 can be carried out again using a replacement adhesive sheet 10 (rework).
[0099] 3B, the member 31 and a member 32 (second adherend) are joined via the adhesive sheet 10 on the member 31 (joining step). An example of the member 32 is a cover film in a display panel.
[0100] Next, as shown in Fig. 3C, the adhesive sheet 10 between the members 31 and 32 is aged (aging step). This step enhances the bonding strength between the adhesive sheet 10 and the members 31 and 32. The aging temperature is, for example, 20°C to 160°C. The aging time is, for example, 1 minute to 21 days. When autoclaving (heat and pressure treatment) is used for aging, the temperature is, for example, 30°C to 80°C, the pressure is, for example, 0.1 to 0.8 MPa, and the treatment time is, for example, 15 minutes or longer.
[0101] According to the adhesive sheet 10, after the bonding step or the aging step, the bonded state between the members 31, 32 can be easily released by using water as necessary.
[0102] By allowing water droplets to penetrate into the interface between the member 31 and the adhesive sheet 10, the adhesive force of the adhesive sheet 10 to the member 31 is reduced, and then the member 32 with the adhesive sheet 10 can be easily separated from the member 31. Thereafter, for example, a replacement member 32 with the adhesive sheet 10 can be bonded to the member 31 via the adhesive sheet 10.
[0103] Alternatively, by allowing water droplets to penetrate into the interface between the member 32 and the adhesive sheet 10, the adhesive force of the adhesive sheet 10 to the member 32 is reduced, and then the member 31 with the adhesive sheet 10 can be easily separated from the member 32. Thereafter, for example, a replacement member 31 with the adhesive sheet 10 can be bonded to the member 32 via the adhesive sheet 10.
[0104] According to adhesive sheet 10, the adhesive strength Fw1 in the first water peel test is 1.2 / 10 mm or less, and therefore rework such as that described above is possible. EXAMPLES
[0105] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".
[0106] Preparation of Acrylic Oligomer M1 First, in a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, a mixture containing 60 parts by mass of dicyclopentanyl methacrylate (DCPMA), 40 parts by mass of methyl methacrylate (MMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred under a nitrogen atmosphere at 70°C for 1 hour. Next, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted under a nitrogen atmosphere at 70°C for 2 hours and then at 80°C for 2 hours (polymerization reaction). Next, the reaction solution was heated at 130°C to volatilize and remove toluene, the chain transfer agent, and unreacted monomers. As a result, a solid acrylic oligomer (oligomer M1) was obtained. The weight average molecular weight of oligomer M1 was 5100, and the glass transition temperature was 130°C. The oligomer M1 is a hydrophobic oligomer.
[0107] Preparation of Acrylic Oligomer M2 First, in a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, a mixture containing 45 parts by mass of DCPMA, 45 parts by mass of MMA, 10 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred under a nitrogen atmosphere at 70°C for 1 hour. Next, 0.2 parts by mass of AIBN as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted under a nitrogen atmosphere at 70°C for 2 hours and then at 80°C for 2 hours (polymerization reaction). Next, the reaction solution was heated at 130°C to volatilize and remove toluene, the chain transfer agent, and unreacted monomers. As a result, a solid acrylic oligomer (oligomer M2) was obtained. The weight average molecular weight of oligomer M2 was 5300, and the glass transition temperature was 115°C. Oligomer M2 is a hydrophilic oligomer.
[0108] Preparation of Prepolymer Composition In a flask, 20 parts by mass of n-butyl acrylate (BA), 70 parts by mass of n-octyl acrylate (NOAA), 8 parts by mass of 4-hydroxybutyl acrylate (4HBA), and 2 parts by mass of N-vinyl-2-pyrrolidone (NVP) were mixed with 0.05 parts by mass of a first photopolymerization initiator (product name "Irgacure 819", bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, manufactured by BASF Japan Ltd.) and 0.05 parts by mass of a second photopolymerization initiator (product name "Irgacure 184", 1-hydroxycyclohexyl phenyl ketone, manufactured by BASF Japan Ltd.), and then the mixture was irradiated with ultraviolet light under a nitrogen atmosphere to polymerize a part of the monomer components in the mixture, thereby obtaining a prepolymer composition with a polymerization rate of about 10%. This prepolymer composition is a partial polymer containing a photopolymerized product (photopolymerized polymer P1a) and a monomer component (residual monomer) that has not undergone a polymerization reaction.
[0109] Example 1 Preparation of Pressure-Sensitive Adhesive Composition Next, 100 parts by mass of the prepolymer composition, 11.5 parts by mass of oligomer M, 0.045 parts by mass of dipentaerythritol hexaacrylate (product name "KAYARAD DPHA", manufactured by Nippon Kayaku Co., Ltd.) as a multifunctional polymerizable compound, 0.3 parts by mass of a first reactive surfactant (product name "Acrit 8WX-046-NS", manufactured by Taisei Fine Chemical Co., Ltd.), and 0.04 parts by mass of an additional photopolymerization initiator (product name "Irgacure 819", manufactured by BASF Japan Ltd.) were mixed to prepare a pressure-sensitive adhesive composition.
[0110] <Preparation of Adhesive Sheet> Next, a pressure-sensitive adhesive composition was applied onto the release-treated surface of a first release liner (product name "Diafoil MRF", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side to form a coating film. Next, the release-treated surface of a second release liner (product name "Diafoil MRN", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached onto the coating film on the first release liner. Next, the coating film between the release liners was irradiated with ultraviolet light from the second release liner side, and the coating film was photocured to form a 50 μm-thick pressure-sensitive adhesive layer (ultraviolet light irradiation process). For ultraviolet light irradiation, a black light lamp (manufactured by Toshiba) was used as the light source, and the illuminance was set to 5.0 mW / cm. 2 The cumulative irradiation dose was 1500 mJ / cm 2 In the ultraviolet irradiation step, a photopolymerization reaction proceeds in the coating film in a reaction system containing the above-mentioned residual monomer and the polyfunctional polymerizable compound, and a photopolymerized polymer P1b having a photocrosslinked structure is formed. In addition, since the photopolymerization reaction proceeds around the above-mentioned photopolymerized polymer P1a, the photopolymerized polymer P1b is formed around the photopolymerized polymer P1a. The pressure-sensitive adhesive layer formed in this step contains such photopolymerized polymer P1a and photopolymerized polymer P1b as base polymers.
[0111] Next, after peeling the first release liner from the adhesive layer, the adhesive layer on the second release liner was dried in a hot air oven at 130°C for 3 minutes. This caused the unreacted monomer in the adhesive layer to volatilize and be removed. Then, after cooling at room temperature, the release-treated surface of a third release liner (product name "Diafoil MRF", thickness 38μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached to the adhesive layer on the second release liner.
[0112] In this manner, the pressure-sensitive adhesive sheet with release liner of Example 1 (second release liner / pressure-sensitive adhesive sheet (thickness 50 μm) / third release liner) was produced.
[0113] Example 2 The pressure-sensitive adhesive sheet with release liner of Example 2 was produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, the blending amount of oligomer M1 was 0.5 parts by mass, 0.5 parts by mass of oligomer M2 was further blended, and 0.5 parts by mass of a second reactive surfactant (trade name "Aqualon KH-10", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was blended in place of the first reactive surfactant.
[0114] Example 3 The pressure-sensitive adhesive sheet with release liner of Example 3 was produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, the blending amount of oligomer M1 was 0.5 parts by mass, 0.5 parts by mass of oligomer M2 was further blended, and 0.3 parts by mass of a second reactive surfactant (Aqualon KH-10) and 0.1 parts by mass of a third reactive surfactant (trade name "Aminoion RE3000MA", manufactured by Nippon Nyukazai Co., Ltd.) were blended in place of the first reactive surfactant.
[0115] Example 4 The PSA sheet with release liner of Example 4 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In preparing the PSA composition, 0.1 part by mass of a third reactive surfactant (Aminoion RE3000MA) was blended in place of the first reactive surfactant.
[0116] Example 5 The pressure-sensitive adhesive sheet with release liner of Example 5 was produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, the blended amount of oligomer M1 was 0.5 parts by mass, 0.5 parts by mass of oligomer M2 was further blended, the blended amount of polyfunctional polymerizable compound (DPHA) was 0.02 parts by mass, and 0.3 parts by mass of a second reactive surfactant (Aqualon KH-10) and 0.1 parts by mass of a first non-reactive surfactant (product name "Rheodol TW-L120", manufactured by Kao Corporation) were blended in place of the first reactive surfactant.
[0117] Example 6 The adhesive sheet with release liner of Example 6 was produced in the same manner as the adhesive sheet with release liner of Example 5, except for the following: In preparing the adhesive composition, 0.1 part by mass of a second non-reactive surfactant (product name "Rheodol TW-L106", manufactured by Kao Corporation) was blended in place of the first non-reactive surfactant (Rheodol TW-L120).
[0118] Example 7 The release-liner adhesive sheet of Example 7 was produced in the same manner as the release-liner adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, the blended amount of oligomer M1 was 0.5 parts by mass, 0.5 parts by mass of oligomer M2 was further blended, the blended amount of polyfunctional polymerizable compound (DPHA) was 0.01 parts by mass, and 0.75 parts by mass of a second reactive surfactant (Aqualon KH-10) was blended in place of the first reactive surfactant.
[0119] Example 8 The PSA sheet with release liner of Example 8 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In preparing the PSA composition, 0.5 parts by mass of Oligomer M2 was mixed in place of Oligomer M1, and 0.5 parts by mass of a second reactive surfactant (Aqualon KH-10) was mixed in place of the first reactive surfactant.
[0120] Example 9 The PSA sheet with release liner of Example 9 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In preparing the PSA composition, oligomer M1 was not blended, and the blended amount of the first reactive surfactant (Acrit 8WX-046-NS) was 0.02 parts by mass.
[0121] Example 10 The pressure-sensitive adhesive sheet with release liner of Example 10 was produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, the blending amount of oligomer M1 was 0.5 parts by mass, 0.5 parts by mass of oligomer M2 was further blended, and 1.0 part by mass of a second reactive surfactant (product name "Aqualon KH-10, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was blended in place of the first reactive surfactant.
[0122] Example 11 The pressure-sensitive adhesive sheet with release liner of Example 11 was produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 3, except for the following: In preparing the pressure-sensitive adhesive composition, the blending amount of the polyfunctional polymerizable compound (DPHA) was set to 0.02 parts by mass.
[0123] [Comparative Examples 1 to 13] Except for preparing the pressure-sensitive adhesive compositions with the compositions shown in Tables 2 and 3, the pressure-sensitive adhesive sheets with release liners of Examples 1 to 13 were produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 1. In Comparative Examples 1 and 2, a silane coupling agent (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) was used.
[0124] <Initial peeling test> An initial peel test was carried out on each of the pressure-sensitive adhesive sheets of Examples 1 to 11 and Comparative Examples 1 to 13 to measure the adhesive strength Fn1. Specifically, the test was performed as follows.
[0125] Preparation steps: First, the third release liner was peeled off from the adhesive sheet with release liner (second release liner / adhesive sheet / third release liner). Next, the adhesive sheet exposed by this was attached to a polyethylene terephthalate (PET) film (product name "Lumirror S10", thickness 50 μm, manufactured by Toray) whose surface had been plasma-treated. This resulted in a laminated film. In the plasma treatment, a plasma irradiation device (product name "AP-TO5", manufactured by Sekisui Kogyo Co., Ltd.) was used, and the voltage was set to 160 V, the frequency was set to 10 kHz, and the treatment speed was set to 5000 mm / min. In the lamination, the adhesive sheet was pressed against the PET film by moving a 2 kg hand roller back and forth once in an environment of 25°C. Next, a laminated film piece with a width of 10 mm and a length of 100 mm was cut out from the laminated film. This laminated film has a PET film, an adhesive sheet piece, and a second release liner in this order in the thickness direction. Next, the second release liner was peeled off from the adhesive sheet piece on the PET film, and the adhesive sheet piece (width 10 mm × length 100 mm) exposed thereby was attached to the tin surface of an alkali glass plate prepared by the float method to obtain a laminate.
[0126] Heat and pressure step: Next, the laminate was subjected to a heat and pressure treatment under conditions of 50° C., 0.5 MPa and 15 minutes, thereby causing the adhesive sheet piece to be pressure-bonded to the alkaline glass plate.
[0127] Settling step: The laminate was then allowed to stand at room temperature for 30 minutes.
[0128] Measurement steps: Next, a 180° peel test was performed to peel the adhesive sheet piece from the alkali glass plate in the laminate, and the force required for peeling (peeling force) was measured. A tensile tester (product name "Autograph AG-50NX plus", manufactured by Shimadzu Corporation) was used for this measurement. Specifically, in this measurement, the adhesive sheet piece was peeled from the alkali glass plate by pulling one end in the length direction of the adhesive sheet piece on the alkali glass plate under the conditions of 25°C, 50% relative humidity, 180° peeling angle, and 300 mm / min pulling speed (first condition), and the adhesive force was measured. The peel length was set to 50 mm, and the average value of the measured peel forces was taken as the adhesive force. The adhesive force Fn1 (N / 10 mm) measured in the measurement step of the initial peel test is shown in Table 1.
[0129] <First water peeling test> A first water peeling test was carried out to measure adhesive strength Fw1 for each of the pressure-sensitive adhesive sheets of Examples 1 to 11 and Comparative Examples 1 to 13. The first water peeling test was the same as the initial peeling test described above, except that the water supplying step described below was carried out after the standing step and before the measurement step. The adhesive strengths Fw1 (N / 10 mm) measured in the measurement step of the first water peeling test are shown in Table 1. The ratio of adhesive strength Fw1 to adhesive strength Fn1 (Fw1 / Fn1) is also shown in Table 1.
[0130] Water supply steps: For the laminate after the standing step, 20 μL of distilled water was supplied onto the alkaline glass plate so that the distilled water was in contact with one longitudinal end of the adhesive sheet piece at the interface between the alkaline glass plate and the adhesive sheet piece.
[0131] <Room temperature peel test> A room temperature peel test was carried out to measure the adhesive strength Fn2 for each of the pressure-sensitive adhesive sheets of Examples 1 to 11 and Comparative Examples 1 to 13. The room temperature peel test was the same as the initial peel test described above, except that in the resting step, the laminate was left to stand at room temperature for 72 hours. The adhesive strength Fn2 (N / 10 mm) measured in the measurement step of the room temperature peel test is shown in Table 1.
[0132] <Second water peeling test> A second water peeling test was carried out on each of the pressure-sensitive adhesive sheets of Examples 1 to 11 and Comparative Examples 1 to 13 to measure the adhesive strength Fw2. The second water peeling test was the same as the first water peeling test described above, except that in the standing step, the laminate was left to stand at room temperature for 72 hours. The adhesive strength Fw2 (N / 10 mm) measured in the measurement step of the second water peeling test is shown in Table 1. The ratio (Fw2 / Fn2) of the adhesive strength Fw2 to the adhesive strength Fn2 is also shown in Table 1. The variation rate (%) of the adhesive strength Fw2 to the adhesive strength Fw1 is also shown in Table 1. This variation rate is calculated by the following formula.
[0133] Fluctuation rate (%) = [(Fw2-Fw1) / Fw1] x 100
[0134] [Table 1]
[0135] [Table 2]
[0136] [Table 3] [Explanation of symbols]
[0137] 10 Adhesive sheet (optical adhesive sheet) H Thickness direction 10a 1st end 10b 2nd end 11 Page 1 12 Side 2 21 Acrylic glass plate 22 water L1, L2 Release liner
Claims
1. An optical adhesive sheet containing a base polymer, the base polymer is a photopolymer of a polymerizable component containing a reactive surfactant, Adhesive strength Fn in the initial peel test below 1 is 1.4N / 10mm or more, Adhesive strength Fw in the first water peel test below 1 An optical adhesive sheet having a strength of 1.2 N / 10 mm or less. Initial peel test: First, a 10 mm wide × 100 mm long adhesive sheet piece of the optical adhesive sheet is attached to an alkaline glass plate prepared by a float process to obtain a laminate (preparation step). Next, the laminate is subjected to a heating and pressurizing treatment under conditions of 50° C., 0.5 MPa and 15 minutes (heating and pressurizing step). Next, the laminate is left to stand at room temperature for 30 minutes (standing step), and then the adhesive sheet piece is peeled off from the alkali glass plate by pulling one end of the adhesive sheet piece in the length direction under the conditions of 25° C., 50% relative humidity, a peeling angle of 180°, and a pulling speed of 300 mm / min, to measure the adhesive strength (measurement step). First water peel test: The test was the same as the initial peel test, except that a water supply step was carried out after the standing step and before the measurement step. In the water supplying step, 20 μL of distilled water is supplied onto the alkaline glass plate of the laminate so that the distilled water contacts one longitudinal end of the adhesive sheet piece at the interface between the alkaline glass plate and the adhesive sheet piece.
2. The optical adhesive sheet according to claim 1 , further comprising a non-reactive surfactant.
3. The optical adhesive sheet according to claim 1 , further comprising a hydrophilic oligomer.
4. In the second water peel test described below, the adhesive strength F 2 and the adhesive force F 1 The adhesive force F 2 The optical adhesive sheet according to claim 1 , wherein the rate of change is 200% or less. Second water peel test: The test was the same as the first water peeling test, except that in the standing step, the laminate was stood at room temperature for 72 hours.
5. The adhesive strength Fn in the following room temperature peel test 2 and the adhesive force Fn 2 The adhesive force F 2 The optical adhesive sheet according to claim 4, wherein the ratio is 0.4 or less. Room temperature peel test: The test was the same as the initial peel test, except that in the standing step, the laminate was stood at room temperature for 72 hours.
Citation Information
Patent Citations
Aqueous adhesive and adhesive sheet
JP2016035023A
Adhesive Composition for Optical Film, Adhesive Layer, Adhesive Optical Film, and Display Device
JP2017528581A
Pressure-sensitive adhesive composition and pressure-senstive adhesive sheet
WO2013129382A1
Water-dispersed acrylic adhesive composition
WO2018043624A1
Layered article and peeling method
WO2021024741A1